Contrast‐enhanced ultrasound of embolic consolidations in patients with pulmonary embolism: A pilot study. Issue 3 (19th October 2015) - Bartelt, Sybille; Trenker, Corinna; Görg, Christian; Neesse, Albrecht
ABSTRACT: Purpose: To analyze and describe the contrast‐enhanced ultrasound (CEUS) patterns of peripheral lung lesions in patients with pulmonary embolism (PE) confirmed on CT angiography or lung scintigraphy. Methods: CEUS had been performed on 35 patients with peripheral lung lesions detected on gray‐scale imaging and confirmed as PE. The following data were evaluated retrospectively: (1) accumulation of contrast medium (absent or present), (2) differentiation between pulmonary arterial (PA) and bronchial arterial blood supply, and (3) contrast‐enhancement pattern (absent/nonhomogeneous or homogeneous). A CEUS pattern of absent or nonhomogeneous enhancement was suspicious (ie, typical) of embolic consolidations (EC), whereas a pattern of homogeneous PA enhancement was considered to be atypical of EC. Results: Peripheral lesions showed a CEUS pattern suspicious of EC in 80% of the patients, with no enhancement in 40% and nonhomogeneous enhancement in another 40%. A CEUS pattern of homogeneous PA enhancement, atypical of EC, was identified in the remaining 20% of the patients. Pulmonary lesions larger than 1 cm showed vascularization more often than smaller lesions did ( p < 0.001). Conclusions: Peripheral lung lesions in patients with confirmed PE show a CEUS pattern of absent or nonhomogeneous contrast enhancement for suspicious EC. Further prospective studies are required to verify the diagnostic accuracy of CEUS for EC. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :129–135, 2016